Antiresonance in (Ni, Zn) ferrite-carbon nanofibres nanocomposites. (11th May 2015) - Fernández-García, Lucía; Suárez, Marta; Luis Menéndez, Jose; Pecharromán, Carlos; Torrecillas, Ramón; Peretyagin, Pavel Y; Petzelt, Jan; Savinov, Maxim; Frait, Zdenek
Abstract: (NiZn)Fe2 O4 carbon nanofiber (CNF) nanocomposites with concentrations up to 5% in volume of CNFs were prepared by traditional ceramic processing and a subsequent spark plasma sintering at 860 °C with a holding time of 1 min. Low-frequency conductivity and magnetic properties were studied, revealing the appearance of a ferromagnetic antiresonance when a certain value of conductivity is reached due to the introduction of a conductive second-phase CNF in the ferromagnetic matrix (ferrite), thereby opening a route to induce magnetically tunable transparency in these composites.